Botanical quality controls and uses of Origanum vulgare L. products and their impact on food security in the province of Jujuy - Argentina - Leila Ayelen Salome GIMENEZ; Nilda Dora Vignale; Marcelo Luis Wagner (Food, Agriculture and Natural Resources - NETWORKS, 2024)
In Argentina, a nation committed to prioritizing food quality, there is a pressing necessity to fortify quality control systems and establish stringent standards ensuring food safety. This study aims to scrutinize commercial samples of Origanum vulgare L. in the province of Jujuy, Argentine Republic, with the objective of assessing their authenticity and overall quality. Both macroscopic and microscopic techniques were employed to analyze composition and verify identity. Simultaneously, a thorough examination of product labels was conducted to ensure compliance with food regulations. Ethnographic techniques, including merchant interviews, were utilized to gather comprehensive insights. The findings reveal considerable variability in the composition of